Tinjauan Hukum Islam terhadap Penayangan Iklan Google dalam Blog - Ali Musthafa; Yayat Rahmat Hidayat (Jurnal Riset Ekonomi Syariah, 2021)
Abstract. This thesis is the result of a library research entitled "Review of Islamic Law Against Displaying Google Adsense Ads in Blogs". This study aims to answer the question of how the process of cooperation agreements and mechanisms for displaying advertisements on blogs, how the implementation of cooperation agreements on displaying advertisements on blogs and how the provisions of Islamic law on cooperation agreements displaying advertisements on blogs. This study aims to determine the mechanism of Google Adsense ads on blogs, the implementation of the contract in the display of Google Adsense ads on blogs, and a review of Islamic law on the Google Adsense ad display contracts on blogs. This type of research uses data collection techniques. The data collected in this research is data that has been obtained during the study by studying books related to problems and interviews with publishers and Google Adsense. The results of the study were then examined using descriptive verification techniques with an inductive mindset, this mindset is used to analyze specific data based on the facts of the research results then general conclusions are drawn. Which reveals the reality of the results of research. The results of this study explain that the collaboration agreement between Publisher and Google Adsense for displaying advertisements on blogs is not valid according to the review of Islamic law, because it does not fulfill several conditions of the syirkah contract, which is association in terms of allowing forbidden things to be prevented, and in terms of the contract object is not it can be seen that the advertisement that will be aired will be in conflict with or not with Islamic law, and this clearly contains the element of gharar (speculative), which will lead to the injury of the principle of 'an taradhin (mutual pleasure / like-like) between the seller and the buyer. Abstrak. Skripsi ini adalah hasil penelitian kepustakaan yang berjudul “Tinjuan Hukum Islam Terhadap Penayangan Iklan Google Adsense dalam Blog”. Penelitian ini bertujuan menjawab pertanyaan tentang bagaimana proses akad kerjasama dan mekanisme penayangan iklan di blog, bagaimana implementasi akad kerjasama terhadap penayangan iklan di blog dan bagaimana Ketentuan hukum Islam terhadap akad kerjasama penayangan iklan di blog. Penelitian ini bertujuan untuk mengetahui mekanisme iklan Google Adsense dalam Blog, implementasi akad dalam penayangan iklan Google Adsense dalam Blog, dan tinjauan hukum Islam terhadap akad penayangan iklan Google Adsense dalam Blog. Jenis penelitian ini menggunakan teknik pengumpulan data. Data yang dikumpulkan dalam penelitian ini adalah data yang telah diperoleh selama penelitian dengan cara mempelajari buku-buku yang berkaitan dengan permasalahan dan wawancara dengan publisher dan google adsense. Hasil penelitian itu kemudian ditelaah dengan menggunakan teknik deskriptif verifikatif dengan pola pikir induktif, pola pikir ini dipakai untuk menganalisis data khusus berdasarkan kenyataan-kenyataan dari hasil riset kemudian diambil kesimpulan yang bersifat umum. Yang mengungkapkan kenyataan kenyataan dari hasil penelitian. Hasil penelitian ini menerangkan bahwa Akad kerjasama antara Publisher dan Google Adsense atas penayangan iklan dalam blog tidak sah menurut tinjuan hukum Islam, karena tidak memenuhi beberapa syarat akad syirkah yaitu berserikat dalam hal yang memungkinkan tidak terhindarnya hal yang diharamkan, dan dari sisi objek akadnya pun tidak dapat diketahui bahwa iklan yang akan ditayangkan nantinya bertentangan atau tidak dengan hukum Islam, dan hal ini jelas mengandung unsur gharar (spekulatif), yang akan mengakibatkan cederanya prinsip ‘an taradhin (saling ridho/suka sama suka) antara penjual dan pembeli.